Freedom and tenure in the academy - Van Alstyne, William W.; Van Alstyne, William W. (Book collections on Project MUSE., 1993)
Questions of academic freedom - from hate speech to the tenure structure - continue to be of great urgency and perennial debate in American higher education. Originally published as a special issue of Law and Contemporary Problems (Summer 1990), this volume draws together leading scholars of law, philosophy, and higher education to offer a first assessment of the founding principles of academic freedom and to define the topic for the 1990s. The original 1940 Statement of Principles on Academic Freedom and Tenure, which has been influential in determining institutional practices for the last half century, has required continual redefinition since its initial declaration. Walter P. Metzger begins this collection with the most complete examination of the 1940 Statement ever provided, shedding light on some of its most troublesome clauses. Following this overview, William W. Van Alstyne presents an "unhurried" historical review of the extent to which academic freedom has been accepted into domestic constitutional law. Two essays deal with the issue of tenure and academic freedom. Ralph S. Brown and Jordan E. Kurland agree that tenure reinforces academic freedom but wonder if there is not a large price to be paid for such a system. In a highly instructive review Matthew Finkin looks at academic tenure and freedom in the light of labor law. Focusing on freedom of artistic expression, Robert O'Neil raises difficult questions about what kinds of art displays taxpayers can be expected to tolerate in the colleges and universities they support. Rodney A. Smolla looks at the ways in which "hate" speech and offensive expression on campuses engage wide First Amendment jurisprudence. Judith Jarvis Thomson examines the vexed issue of selecting - and valuing - individual faculty members or disciplines with regard to ideology. Michael W. McConnell offers a spirited defense of the value of allowing religiously committed colleges and universities to pursue their own course in a secular age. New to this edition, Thomson and Finkin offer an equally spirited response to McConnell. Returning to larger questions, David M. Rabban discusses the clash between institutional and individual claims of academic freedom. Also included are reprints of the full texts of the 1915 and 1940 statements, as well as all extensive bibliography. Freedom and Tenure in the Academy is sure to be an essential volume for all those - lawyers, scholars, and administrators of higher education alike - concerned with the difficult issues of academic freedom facing the world of higher education.